Growing Apart, Losing Trust? : The Impact of Inequality on Social Capital - Gould, Eric (IMF Working Papers; Working Paper ;, 2016)
There is a widespread perception that trust and social capital have declined in United States as well as other advanced economies, while income inequality has tended to increase. While previous research has noted that measured trust declines as individuals become less similar to one another, this paper examines whether the downward trend in social capital is responding to the increasing gaps in income. The analysis uses data from the American National Election Survey (ANES) for the United States, and the European Social Survey (ESS) for Europe. Our analysis for the United States exploits variation across states and over time (1980-2010), while our analysis of the ESS utilizes variation across European countries and over time (2002-2012). The results provide robust evidence that overall inequality lowers an individual's sense of trust in others in the United States as well as in other advanced economies. These effects mainly stem from residual inequality, which may be more closely associated with the notion of fairness, as well as inequality in the bottom of the distribution. Since trust has been linked to economic growth and development in the existing literature, these findings suggest an important, indirect way through which inequality affects macro-economic performance.